Implementation of Zakat Mal Management Based on Law Number 23 Year 2011 in Institution Amil Zakat Muhammadiyah, Medan City - Nispul Khoiri; Ramadhan Syahmedi Srg; Izhar Izhar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to find the problems and strategies carried out by the Lazis Muhammadiyah management in Medan are divided into two, namely internal and external. And what is being done is an effort to raise awareness together to channel zakat al-mal to Lazis Muhammadiyah so that it is managed properly and transparently and evenly so that it directly touches the community so that the objectives of the zakat law are realized. Management of zakat based on Law Number 23 of 2011 is zakat management states that zakat management aims to increase the effectiveness and efficiency of services in managing zakat; and increase the benefits of zakat to create social welfare and poverty alleviation. Efforts to realize the function and role of zakat in the welfare of society, the zakat management law issued by the government is in principle to facilitate, motivate and confirm the management of zakat issued by the Amil Zakat Agency or the Amil Zakat Institute.